Immunopathology of Autoimmune Hemolytic Anemia: A Systematic Review of Molecular Mechanisms and Emerging Therapeutic Strategies - Al Sayeh, Ahmad Maher Ibrahim; Rawashdeh, Mohammad (Journal of Biomedicine and Biochemistry, 2025)
Autoimmune hemolytic anemia (AIHA) has become recognised as a complex and heterogeneous disease characterised by a wide range of immunopatholog- ical and biochemical mechanisms. Several treatment options exist in the field of AIHA however; there is as yet little or no evidence of therapeutic strategies targeted on molecular aspects of the disease. An up-to-date comprehensive sys- tematic review covering immunopathology for emerging areas of experimental therapy of AIHA will help direct future research and optimize clinical deci- sions, by focusing on issues needing improvement. This structured systematic review will focus on the immunopathological molecular mechanisms and the most recent emerging therapeutic strategies for AIHA or emerging therapeu- tic strategies targeted at the molecular mechanisms of the disease. The aim of the review is to collect, critically evaluate, and systematically summarise all available evidence on the immunopathology and experimental therapy of AIHA. For the immunopathology of AIHA, the main issues of interest are: the initiation and development of the disease, the immunological and biological mechanisms of red blood cell destruction, diagnostic markers predicting the response to therapy, the relationship with other autoimmune disorders and aspects of the genetics of AIHA. Experimental therapy will include newly ap- plied or planned treatment protocols and compounds, or medications present- ing disease-modifying and non-conventional mechanisms of action. This review will be oriented toward researchers and clinicians engaged in the management and research of AIHA, and results will be analysed and presented in light of their potential to translate findings into practice. Eligibility for inclusion criteria, salience assessment, and data extraction analysis aims to critically synthesize available data, identify research gaps and assess the quality of ev- idence. Substantial advances in the comprehension of the immunopathology of the disorder or the emergence of new advanced science verified drugs and other compounds in therapy will be explored. Summarised results will point toward research fields most urgently needing further investigation and provide a comprehensive synthesis of evidence helpful for the optimization of clinical decisions and the initiation of innovative therapies.